Macrophage LAMTOR1 Deficiency Prevents Dietary Obesity and Insulin Resistance Through Inflammation-Induced Energy Expenditure - Ying, Lingwen; Zhang, Mingliang; Ma, Xiaojing; Si, Yiming; Li, Xiaoya; Su, Jiaorong; Yin, Jun; Bao, Yuqian (Frontiers in Cell and Developmental Biology, 2021)
Here, we studied the metabolic function of LAMTOR1 from macrophages using LAMTOR1 macrophage-specific knockout (MKO) mice. LAMTOR1 MKO mice showed resistance to high-fat diet (HFD)-induced obesity, lipid steatosis, and glucose metabolic disorders, with elevated levels of pro-inflammatory cytokines. The energy expenditure, oxygen consumption, and CO2 production increased significantly in HFD-fed MKO vs. wild-type (WT) mice. HE and immunohistochemistry staining showed a remarkable CD68+ Kupffer cell accumulation in the liver. Additionally, flow cytometry revealed that the proportion of macrophages and monocytes increased significantly in the liver of MKO mice. Of note, these macrophages were probably derived from the bone marrow since the proportion of CD11b+ cells as well as the proliferative activity was also increased in the context of femoral bone marrow cells. In addition, the Kupffer cells of both WT and KO mice were double-positive for the M1 (CD86) and M2 (CD206) markers. However, the expression of both M1 and M2 macrophage-related genes was increased in the liver of HFD-fed KO mice. Murine primary hepatocytes and Kupffer cells were further isolated and incubated with oleic acid for 24 h. The glucose output of primary hepatocytes from MKO mice was not affected. However, decreased lipid tolerance was observed in LAMTOR1-deficient Kupffer cells. Overall, our results suggest that LAMTOR1 deficiency in macrophages prevents obesity and metabolic disorders via the accumulation of Kupffer cells in the liver and the consequent hyper-inflammation and increased energy expenditure. Therefore, our results provide a new perspective for macrophage-derived LAMTOR1 in the context of systemic metabolism.